2018
DOI: 10.1177/1470785317752048
|View full text |Cite
|
Sign up to set email alerts
|

Behind the ratings: Text mining of restaurant customers’ online reviews

Abstract: Establishing the relation between online ratings and reviews provides a potentially inexpensive and effective way for restaurants to capture quality improvement hints from customers. To this end, this study proposes an integrated approach that leverages text mining and empirical modeling to quantitatively correlate ratings with reviews. From Dianping.com (a Chinese crowd-sourced online review community), 49,080 pairs of restaurant rating and review were examined, with high-frequency words, major topics, and su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 54 publications
(48 citation statements)
references
References 36 publications
0
39
0
Order By: Relevance
“…The data generated from food delivery apps can be used for optimizing delivery route for reducing the time consumption of the consumers, identifying individual's ordering behavior online, and improving food services. For example, Jia () examined restaurant customers’ ratings and reviews, and identified high‐frequency words, major topics, and subtopics using text mining. It has proven that digital text data analytics is a cost‐effect approach for restaurants to gain quality improvement ideas from customers.…”
Section: Application Of Text Data In Food‐related Studiesmentioning
confidence: 99%
“…The data generated from food delivery apps can be used for optimizing delivery route for reducing the time consumption of the consumers, identifying individual's ordering behavior online, and improving food services. For example, Jia () examined restaurant customers’ ratings and reviews, and identified high‐frequency words, major topics, and subtopics using text mining. It has proven that digital text data analytics is a cost‐effect approach for restaurants to gain quality improvement ideas from customers.…”
Section: Application Of Text Data In Food‐related Studiesmentioning
confidence: 99%
“…In hospitality and tourism studies, sentiment analysis has been the most popular application in automated text analysis [8,9,12]. However, review sentiments can be redundant due to most review platforms (such as Airbnb, TripAdvisor, and online travel agencies) requiring numeric ratings, which can also serve as an accurate representation of the overall sentiment [15,18,49]. In addition, a single written review often consists of different topics and mixtures of sentiments [16].…”
Section: Automated Text Analysismentioning
confidence: 99%
“…In that properties of service, therefore, perceived service evaluation or recommendation can be crucial indicators in the field of aviation industry. Jia [13] has conducted text mining though a Chinese crowd-sourced online review community, and 49,080 pairs of restaurant ratings and reviews were examined, with high-frequency words, major topics, and subtopics identified. After text mining, multilinear regression was employed to screen out the most impactful factors that influence taste, environment, and service ratings.…”
Section: Consumers' Evaluation Criteria Onmentioning
confidence: 99%